Impact Assessment of Storm Surge and Climate Change-Enhanced Sea Level Rise on Atoll Nations: A Case Study of the Tarawa Atoll, Kiribati - Sabūnas, Audrius; Miyashita, Takuya; Fukui, Nobuki; Shimura, Tomoya; Mori, Nobuhito (Frontiers in Built Environment, 2021)
The Pacific region consists of numerous Small Island Developing States (SIDS), one of the most vulnerable to flooding caused by compound effects of sea level rise (SLR) and storms. Nevertheless, individual studies regarding the impact assessment for SIDS, such as the low-lying Kiribati, remain scarce. This study assessed the impact of climate change-induced storm surge and SLR compounding effects on Tarawa, the most populous atoll of Kiribati, the largest coral atoll nation. It projected the impact using a combined dynamic surge and SLR model based on the IPCC AR5 RCP scenarios and 1/100 and 1/50 years return period storm events. This approach allows estimating the inundation scope and the consecutive exposed population by the end of the 21st century. The results of this study show that the pace of SLR is pivotal for Tarawa, as the sea level rise alone can claim more than 50% of the territory and pose a threat to over 60% of the population under the most intense greenhouse gas emissions scenario. Furthermore, most coasts on the lagoon side are particularly vulnerable. In contrast, the contribution of extreme events is generally minimal due to low wind speeds and the absence of tropical cyclones (TC). Despite this, it is clear the compound effects are critical and may inescapably bring drastic changes to the atoll nations by the end of this century. The impact assessment provided in this study draws attention to the climate change-induced social impact on SIDS and evaluating their adaptation potential.